Building Women's Economic and Social Empowerment through Enterprise : An Experimental Assessment of the Women's Income Generating Support Program in Uganda - Blattman, Christopher; Green, Eric; Annan, Jeannie; Jamison, Julian (World Bank, Washington, DC, 2014)
This study investigates an attempt to economically and socially empower some of the poorest and most vulnerable young women in one of the poorest and most fragile places in the world: northern Uganda. Investing in women is said to be a key to development. Educate her, buy her a cow or goat, or help her start a business and great things will follow: sustained increases in income, greater empowerment and social inclusion, health and education for the children, and (especially in war-affected regions) mental health and happiness. This report provides provisional answers to these questions based on data collected from April 2009 to August 2012. The questions will continue to be explored and analyzed in academic papers in future, but the authors attempt to draw out the key findings and policy lessons as close to the end of the intervention and data collection as possible.